1991
DOI: 10.1002/cne.903040209
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the cecum in the lateral dorsal motor nucleus of the vagus nerve and commissural subnucleus of the nucleus tractus solitarii in rat

Abstract: Motor fibers of the accessory celiac and celiac vagal branches are derived from the lateral columns of the dorsal motor nucleus of the vagus nerve. These branches also contain sensory fibers that terminate within the nucleus of the tractus solitarii. This study traces the innervation of the intestines by using the tracer cholera toxin-horseradish peroxidase. In 53 rats, the tracer was injected into either the stomach, duodenum, jejunum, terminal ileum, cecum, or ascending colon. With all cecal injections, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
82
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(89 citation statements)
references
References 67 publications
7
82
0
Order By: Relevance
“…These neurons are the second group of extrinsic innervation to the ileum. Parasympathetic preganglionic neurons in the DMNV projected to the duodenum, jejunum and ileum in the rat [1,33] and cat [26]. However, the number of labeled neurons after injections into the small intestine was much smaller than that after stomach injections [1,26,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These neurons are the second group of extrinsic innervation to the ileum. Parasympathetic preganglionic neurons in the DMNV projected to the duodenum, jejunum and ileum in the rat [1,33] and cat [26]. However, the number of labeled neurons after injections into the small intestine was much smaller than that after stomach injections [1,26,33].…”
Section: Discussionmentioning
confidence: 99%
“…After injection of horseradish peroxidase (HRP) into the small intestine of the cat [5], dog [14] and monkey [29], labeled sensory neurons were found in the dorsal root ganglia (DRGs) and/or nodose (vagal distal) ganglion (NG). Parasympathetic preganglionic neurons innervating the small intestine of the rat [1,33] and cat [26] were located in the dorsal motor nucleus of the vagus nerve (DMNV).…”
mentioning
confidence: 99%
“…Studies on the innervation of the NTS have suggested that functionally classified columns are arrayed rostrocaudally in this nucleus; for example, gustatory afferents occupy the rostral third portion of the column (Whitehead and Frank, 1983; Hamilton and Norgren, 1984), while visceral afferents occupy a more caudal region (Kalia and Mesulam , 1980; Panneton and Loewy, 1980;Ciriello, 1983 Altschuler et al , 1989Altschuler et al , , 1991. Based on neurological studies showing that the NTS controls the gastrointestinal tract via the dorsal motor nucleus of the vagus (DMV) (Morest, 1967;Cottle and Calaresu, 1975;Norgren, 1978;Beckstead et aL, 1980;Rogers et aL, 1980;Arends et al , 1988), and controls the pharynx, larynx, and esophagus via the nucleus ambiguus (Amb) (Morest, 1967;Cottle and Calaresu, 1975 Cunningham et al, 1991), the NTS appears to play an important role as the afferent system of all visceromotor reflexes, including the emetic response.…”
mentioning
confidence: 99%
“…The subnuclei of the NTS are viscerotopically organized [1,2,5]; however, the same subnucleus might receive sensory information from more than one peripheral organ [1,[5][6][7]11,16,22,25,30]. The subnucleus centralis (cNTS), however, receives sensory inputs originating almost exclusively from esophageal afferent fibers [1,8,9,16,23], thus, this nucleus may be a possible model for the study of NTS neurons devoted to the control of esophagus-mediated reflexes.…”
Section: Discussionmentioning
confidence: 99%
“…Vagal sensory afferent fibers enter the brainstem via the tractus solitarius and terminate in a viscerotopically organized manner in the subnuclei of the nucleus tractus solitarius (NTS) [1,2,5]. Although sensory inputs from distinct peripheral organs, such as, for example, the aortic branch and the stomach, do not converge on single NTS neurons [26], the same subnucleus may receive sensory information from more than one peripheral organ.…”
Section: Introductionmentioning
confidence: 99%